Simple starch-gel electrophoresis of gliadin proteins using the LKB-multiphor system - Kocna, Petr; Holáková-Kočová, Marie; Šašek, Antonín (Zeitschrift für Lebensmittel-Untersuchung und -Forschung, 1983)
A simple modification of the horizontal starch-gel electrophoresis of gliadin proteins with the use of LKB Multiphor System has been developed. The thin-layer starch gel is prepared by using the original gel-moulding cassette and the procedure on the whole is easier. The sensitivity is comparable with that of the original method. Our modification moreover widens the field of application of the LKB Multiphor System.
Keywords: Electrophoresis, Starch Gel; Gliadin; gliadin; ektroforéza na škrobovém gelu